2021
DOI: 10.1007/s10815-021-02067-7
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation for genetic diseases leading to premature ovarian insufficiency (POI)

Abstract: Purpose The current review aims to summarize the data available concerning the applicability of fertility preservation techniques to genetic conditions at risk of premature ovarian insufficiency (POI). Methods A literature review through the PubMed Database was carried out. Results About 10% of cases of POI is related to genetic diseases. The most frequent conditions associated with POI are Turner syndrome and fragile X pre-mutation; mutation of BRCA 1-2 genes and several other mutations and genetic syndromes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 139 publications
(240 reference statements)
0
28
0
3
Order By: Relevance
“…Ovarian tissue cryopreservation may be an option to preserve fertility in prepubertal girls and young women who require immediate chemotherapy. It has some advantages, especially for prepubertal patients: no need for ovarian stimulation, thus, no further risk for estrogen-sensitive cancer types, and preservation of more and better-quality primordial follicles of the ovarian cortex [ 38 , 39 ]. After 2018, there was a shift from hormone replacement therapy to more innovative treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian tissue cryopreservation may be an option to preserve fertility in prepubertal girls and young women who require immediate chemotherapy. It has some advantages, especially for prepubertal patients: no need for ovarian stimulation, thus, no further risk for estrogen-sensitive cancer types, and preservation of more and better-quality primordial follicles of the ovarian cortex [ 38 , 39 ]. After 2018, there was a shift from hormone replacement therapy to more innovative treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with genetic risk of POI, novel methods aiming at fertility preservation can benefit them a lot through early diagnosis. Recent research, for instance, revealed that there was close correlation between POI and the mutations of BRCA [ 46 ]. BRCA can bind to various essential regulatory proteins and regulate gene expression [ 47 ], which make it possible for BRCA to play a novel role in the regulation of autophagy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is unquestionable evidence that puberty disorders and menstrual cycle abnormalities, endometriosis, PCOS, subfertility, and POI as well as adverse pregnancy outcomes are multifactorial, with a strong genetic predisposition modulated by the actual ED exposure [80][81][82][83]. However, experimental studies on TCDD effects clearly suggest that ancestral ED exposure through transgenerational epigenetic inheritance may also play a significant role in the pathophysiology of all female reproductive disorders, and this needs to be considered.…”
Section: F3 Females Paternal Germline Paternal and Maternal Germline Maternal Germlinementioning
confidence: 99%